Month-by-month baby book in-depth, monthly advice on your baby's growth, care, and development in the first year. (New York, NY DK Publishing, 2023)
"A comprehensive, illustrated guide to the extraordinary first year of a baby's life for new parents The only book new parents will need for the extraordinary first year of their baby's life. This comprehensive book covers every moment of the first twelve months of your baby's life - from their first moments at home, feeding, and sleeping arrangements, to travelling, building their body strength, and starting to eat solids. A team of expert paediatricians, midwives, psychologists, and nutritionists provide unrivalled detail on everything new parents can expect. This new edition has been updated with the latest medical advice for a new generation of parents, and includes reassuring answers to common questions, offering additional support for whenever you need it"--Publisher's description.
Your new baby -- Being a parent -- Babycare basics -- Your baby month by month -- Your baby from birth to 3 months -- Your baby from 4 to 6 months -- Your baby from 7 to 9 months -- Your baby from 10 to 12 months -- Your baby's health -- Your unwell baby -- Illness & injuries.
Includes index.
112755
Keywords: Infants -- Care; Newborn infants -- Care; Parenting